Calanus® Oil. Utilization, composition and digestion - Pedersen, Alice Marie (UiT The Arctic University of Norway, 2016)
The papers I and II of this thesis are not available in Munin. Paper I: Pedersen, A. M., Vang, B., Olsen, R. L.: «Oil from Calanus finmarchicus —Composition and Possible Use: A Review.” Available in Journal of Aquatic Food Product Technology 2014, 23(6):633-646. Paper II: Vang, B., Pedersen, A.M., Olsen, R.L.: “Oil extraction From the Copepod Calanus finmarchicus Using Proteolytic Enzymes.” Available in Journal of Aquatic Food Product Technology 2014, 22(6):619-628 In the pelagic system, phytoplankton are the main producers of n-3 LC-PUFA and make up the foundation of the oceanic food web. Zooplankton, such as copepods and krill, are the most numerous primary consumers in the marine environment and have a central role in the energy transfer to higher trophic levels. The copepod Calanus finmarchicus is present in large amounts in the North Atlantic and has lipid-rich stages that can be harvested in a sustainable manner. The aim of this thesis was to provide knowledge which could contribute to the commercial utilization of Calanus finmarchicus. The wax ester-rich oil may be used as an alternative lipid source to fish oil in feeds for aquaculture, leading to good growth and efficient nutrient utilization. Moreover, the oil can be used as a health promoting nutraceutical as several recent publications indicate that oil from C. finmarchicus may have beneficial health effects beyond those which may be ascribed to the intake of EPA and DHA alone. In this work it was investigated if the use of commercial proteolytic enzymes could improve oil recovery from C. finmarchicus in an industrial-like process, and to characterize the oil obtained. The results showed a substantially higher oil yield with the use of proteolytic enzymes compared to standard fish oil production technology. The main components of the oil extracted from C. finmarchicus are monoesters of long-chain fatty acids and fatty alcohols, namely wax esters. In addition, the oil is rich in the deep red antioxidant astaxanthin present mostly as di- and ...